PERSON-ORGANIZATION FIT, AS MEDIATED BY KNOWLEDGE SHARING BEHAVIOR, AND INTRINSIC MOTIVATION ON INNOVATIVE WORK BEHAVIOR - Rizky Aulia Hidayah Syafranuddin; Ramadhani Hamzah; Efendi Rahmanto (Jurnal Ekonomi, 2023)
This study aims to examine the relationship between Person Organization Fit mediated by Knowledge Sharing Behavior and Intrinsic Motivation on Innovative Work Behavior. This study uses a quantitative approach using a questionnaire. Questionnaires were given to 68 respondents who were employees of the West Java Province Population and Civil Registration Service. The data analysis method that will be carried out consists of descriptive statistical tests, outer model tests consisting of (convergent validity, discriminant validity, composite reliability). As well as testing the hypothesis using the Structural Equation Modeling (SEM) full model analysis with smartPLS. In the full Structural Equation Modeling model in addition to confirming the theory, also explains whether or not there is a relationship between latent variables evaluated by t-test and significance. The results showed that there was no significant effect of person organization fit (organizational and individual fit) on innovative work behavior through intrinsic motivation. On the other hand, a significant influence was found from person organization fit (organizational and individual fit) on innovative work behavior innovative) through knowledge sharing behavior (knowledge sharing behavior).